Seasonal variations of biogenic secondary organic aerosol tracers in Cape Hedo, Okinawa. (April 2016) - Zhu, Chunmao; Kawamura, Kimitaka; Fu, Pingqing
Abstract: Secondary organic aerosol (SOA) substantially contributes to particulate organic matter affecting the regional and global air quality and the climate. Total suspended particle (TSP) samples were collected in October 2009 to February 2012 on a weekly basis at Cape Hedo, Okinawa, Japan in the western North Pacific Rim, an outflow region of Asian aerosols and precursors. The TSP samples were analyzed for SOA tracers derived from biogenic volatile organic compounds (BVOCs). Total isoprene-SOA tracers showed a maximum in summer (2.12 ± 2.02 ng m −3 ) and minimum in winter (1.16 ± 0.92 ng m −3 ). This seasonality is mainly controlled by isoprene emission from the local subtropical forest, followed by regional scale emission of isoprene from the surrounding seas and long-range transported air masses. Total monoterpene-SOA tracers peaked in March (3.38 ± 2.03 ng m −3 ) followed by October (2.95 ± 1.62 ng m −3 ). In contrast, sesquiterpene-SOA tracer, β-caryophyllinic acid, showed winter maximum (1.63 ± 1.18 ng m −3 ) and summer minimum (0.20 ± 0.46 ng m −3 ). The variations of the monoterpene- and sesquiterpene-SOA tracers are likely related to the continental outflow of oxidation products of BVOC. Using a tracer-based method, we estimated the total biogenic SOC of 0.25–157 ng m −3 (mean 35.8 ng m −3 ) that accounts for 0.01–9.8% (mean 2.7%) of aerosol organic carbon. Our study suggests that SOA formation in the western North Pacific Rim is involved with not only local but also regional emissions followed by long-range atmospheric transport. Highlights: Maximum isoprene-SOA in summer is controlled by local source. Monoterpene- and sesquiterpene-SOA are related to the continental outflow. Biogenic SOC accounts for 0.01–9.8% of aerosol organic carbon.